Assessing effective half-life of I-131 in 39 thyroid cancer patients at Dong Nai General Hospital - Nguyen , Tan Duoc; Do , Ha Phuong; Tran , Pham Ngoc Trinh (Nuclear Science and Technology, 2026)
Radioiodine therapy to kill the residual cells after surgery in thyroid cancer patients is a widespread treatment method nowadays. Despite the therapeutic benefits, the amount of I-131 that remains in the patient’s body also causes radiation risks to caregivers and persons in close contact. This study assesses the effective half-life () of I-131 in 39 patients who underwent thyroid cancer treatment at Dong Nai General Hospital. Radioactive activity on the patient’s body was measured by survey meter GAL20-C (ELSE SOLUTIONS), placed 1.0 meters away from the patient, at 0.5; 2.0; 4.0; 6.0; 24.0 hours; and 7 days after administration. The measurement data was fitted by a mono-exponential function respecting time by the least squares method to figure out the effective half-life. The result function has a good coefficient of determination, , were (high-activity group), and (low-activity group). The effective half-life was proved to be different between these two groups of patients.